Examination of the Glycine Betaine-Dependent Methylotrophic Methanogenesis Pathway: Insights Into Anaerobic Quaternary Amine Methylotrophy - Creighbaum, Adam J.; Ticak, Tomislav; Shinde, Shrameeta; Wang, Xin; Ferguson, Donald J. (Frontiers in Microbiology, 2019)
Recent studies indicate that environmentally abundant quaternary amines (QAs) are a primary source for methanogenesis, yet the catabolic enzymes are unknown. We hypothesized that the methanogenic archaeon Methanolobus vulcani B1d metabolizes glycine betaine (GB) through a corrinoid-dependent GB:coenzyme M (CoM) methyl transfer pathway. The draft genome sequence of M. vulcani B1d revealed a gene encoding a predicted non-pyrrolysine MttB homolog (MV8460) with high sequence similarity to the GB methyltransferase encoded by Desulfitobacterium hafniense Y51. MV8460 catalyzes GB-dependent methylation of free cob(I)alamin indicating it is an authentic MtgB enzyme. Proteomic analysis revealed that MV8460 and a corrinoid binding protein (MV8465) were highly abundant when M. vulcani B1d was grown on GB relative to growth on trimethylamine. The abundance of a corrinoid reductive activation enzyme (MV10335) and a methylcorrinoid:CoM methyltransferase (MV10360) were significantly higher in GB-grown B1d lysates compared to other homologs. The GB:CoM pathway was fully reconstituted in vitro using recombinant MV8460, MV8465, MV10335, and MV10360. Demonstration of the complete GB:CoM pathway expands the knowledge of direct QA-dependent methylotrophy and establishes a model to identify additional ecologically relevant anaerobic quaternary amine pathways.